A comparison of reading on-line and paper documents - O'Hara, Kenton; Sellen, Abigail (Proceedings of CHI '97 ( Atlanta, GA.), 1997)
We report on a laboratory study that compares reading from paper to reading on-line. Critical differences have to do with the major advantages paper offers in supporting annotation while reading, quick navigation, and flexibility of spatial layout. These, in turn, allow readers to deepen their understanding of the text, extract a sense of its structure, create a plan for writing, cross-refer to other documents, and interleave reading and writing. We discuss the design implications of these findings for the development of better reading technologies.